In Vitro Regio- and Stereoselective Oxidation of β-Ionone by Human Liver Microsomes - Marumoto, Shinsuke; Shimizu, Ryoyu; Tanabe, Genzoh; Okuno, Yoshiharu; Miyazawa, Mitsuo (Planta Medica, 2017)
The metabolism of the norisoprenoid β-ionone was investigated in vitro using human liver microsomes and 11 different recombinant cytochrome P450 enzymes expressed in Trichoplusia ni cells. β-Ionone was found to be oxidized via 4S-hydroxylation by CYP2B6 in human liver microsomes. CYP1A2 also regioselectively catalyzed the hydroxylation of β-ionone to yield 4-hydroxylation; this conversion was not stereoselective. Further kinetic analysis revealed that CYP2B6 exhibited the highest activity for β-ionone 4-hydroxylation. Kinetic analysis showed that Km and Vmax for oxidation of β-ionone by CYP1A2 and CYP2B6 was 107.9 ± 36.0 µM and 3200.3 ± 323.0 nmol/min/nmol P450 and 5.6 ± 1.2 µM and 572.8 ± 29.8 nmol/min/nmol P450, respectively. The reaction rates observed using human liver microsomes and recombinant CYP2B6 were very high compared with those of other CYP2B6 substrates reported thus far. These results suggest that β-ionone, a norisoprenoid present in nature, is one of the effective substrates for CYP2B enzymes in human liver microsomes. To the best of our knowledge, this is the first time that 4-hydroxy β-ionone has been described as a human metabolite of β-ionone.
Keywords: β-ionone; human liver microsome; cytochrome P450; regio- and stereoselective oxidation; 4-hydroxy-β-ionone